CENOZOIC TECTONICS AND SEISMICITY OF THE NORTHWESTERN PART OF THE ISSYK-KUL' BASIN (TIEN SHAN) - Korzhenkov A.M. (My University, 2000)
The paper presents new pre-neotectonic and neotectonic data obtained by conventional methods of geology and geomorphology as well as fission track analysis used for dating tectonic uplifts for the first time in Kyrghyzstan. It has been concluded that the setting of extension that acted upon the region during most of the Paleogene gave way to submeridional compression in the Cenozoic. Analysis of main morphologic and structural parameters of neotectonic features permitted estimation of the extent and rate of crustal shortening in the west of the Issyk-Kul' basin.
Keywords: Cenozoic; Cenozoic; Кайнозой